Optimization of Soy Protein Hydrolysis with Papain Enzyme and Its Cytotoxic Activity Against MCF-7 Cancer Cells - Sandra Hermanto; Syadzwina Nurdzakiyyah Ahmad; Tarso Rudiana (Jurnal Sains Farmasi & Klinis, 2023)
Soybean is a source of vegetable protein that is rich in nutrients and a source of producing anticancer bioactive peptides. This study aims to determine the optimum conditions for hydrolysis of soybean protein with papain enzyme and their cytotoxicity against the MCF-7 cells. Soybean protein was isolated using an acid precipitation technique. Then, the protein isolate was hydrolyzed using papain enzyme with variations of papain concentration 0,5; 1; and 5% (v/v) and variations of incubation time 0, 1, 2, 3, and 4 hours at 50 °C. The hydrolysates were tested for their degree of hydrolysis (%DH), molecular weight profile using SDS-PAGE, and cytotoxicity against the MCF-7 cells through an in-vitro assay. The most active hydrolysate was fractionated using Sephadex G-15 and characterized by the molecular weight by LCMS/MS. The result showed that the optimum condition for hydrolysis was 1% (v/v) of enzyme concentration and 3 hours of incubation time with a %DH value of 3.01%. Based on the SDS-PAGE result, the hydrolysate had protein bands in a lower range (<25 kDa). That hydrolysate has cytotoxicity with an IC50 value of 1.87 mg/mL, and the molecular weight of its bioactive peptide is 7.70 kDa.